On the significance of Surfactant Protein-A within the human lungs - Lang Dagmar S; Abdullah Mahdi; Schultz Holger; Kähler Daniel; Goldmann Torsten; Stellmacher Florian; Vollmer Ekkehard (BMC, 2009)
Abstract Surfactant Protein-A (SP-A) is the most prominent among four proteins in the pulmonary surfactant-system. SP-A is expressed by alveolar epithelial cells type II as well as by a portion of non small cell lung carcinomas (NSCLC). The expression of SP-A is complexly regulated on the transcriptional and the chromosomal level. SP-A is a major player in the pulmonary cytokine-network and moreover has been described to act in the pulmonary host defense. By the use of cell culture or animal models the functional properties have been repeatedly shown in many aspects, often bearing surprising properties which strongly indicate the physiological importance of SP-A. To date SP-A is recognized as a molecule essential for pulmonary development, structure and function. An upcoming number of reports deals with the role of SP-A for pulmonary pathology. This article gives an overview about the state of knowledge on SP-A focused in applications for human pulmonary disorders and points out the importance for pathology-orientated research approaches using immunohistochemistry or in situ hybridization as promising methods to further elucidate the role of this molecule in adult lung diseases.